Cartographie des changements de la couverture végétale dans les aires protégées du Ferlo (Nord Sénégal) : cas de la réserve de biosphère - Diara Sylla; Taibou Ba; Aliou Guisse (Physio-Géo)
The study presents land cover maps of the Ferlo Biosphere Reserve (created in 2012) made by visual interpretation from satellite images (Arcgis and Corona) taken in 1965 and 2017. Twelve land cover patterns (or classes) were identified: riparian relic forest, woody savannah, tree savannah, shrub savannah with trees, shrub savannah, tree steppe, shrub steppe with trees, shrub steppe, bare soil and rock, rainfall crop and fallow, habitat, pond. The spontaneous vegetation formations covered 96 % of the total area in 1965 and still more than 94 % in 2017. However this stability of the land cover by the spontaneous vegetation, was accompanied by a strong evolution of the different types of cover. Of the nearly 1,914,000 ha inhabited by spontaneous vegetation in 1965, 38.2 % retained the same land cover class between the two dates, 42.1 % have decreased (especially in the north and extreme south) and 19.7% have increased (especially in the south-west). Shrub savannahs with trees remain dominant (about 687 000 ha in 1965, about 603 000 ha in 2017), but the shrub steppes have increased significantly (about 240 000 ha in 1965, about 497 000 ha in 2017). We find here the degradation of vegetation cover common to all the Sahel. More than natural conditions (the drought that appeared in the early 1970s), this evolution seems to be due in Ferlo to the presence, now continuously, of formerly transhumant populations.